Effectiveness Evaluation of Using Unmanned Aerial Vehicles (Drones) in Topographic Maps Production - زلخا ليمار; عمر الخليل; محسن أحمد (Latakia University Journal -Engineering Sciences Series, 2024)
With the increasing use of Unmanned Aerial Vehicles (Drones) in various fields nowadays, especially in mapping, there is a need for organized mechanisms and methodologies to assess the accuracy of this technology, as it is influenced by various factors. This study discusses the latest developments in processing drones’ images for photogrammetric applications and mapping, focusing on using the latest standards to evaluate the accuracy of products derived from drones’ images, such as Digital Terrain Models used to generate contour lines and orthophotos that represent the necessary base map for drawing the required map .and some theoretical concepts related to the use of drones for producing topographic maps were presented. The results of a case study conducted in Ain Al-Fijah area in Syria demonstrated the effectiveness of this technology, with overall accuracy of aerial triangulation 9.7 cm. Regarding vertical accuracy of Digital Terrain Model, and horizontal accuracy of orthophoto, they reached 23.7 cm and 15.5 cm respectively meeting American standards (ASPRS), which are the latest available standards for evaluating the accuracy of drones’ products. This is an acceptable accuracy for obtaining topographic maps at a scale of 1:10000.